Ganglion Cell-Inner Plexiform Layer, Peripapillary Retinal Nerve Fiber Layer, and Macular Thickness in Eyes with Myopic β-Zone Parapapillary Atrophy - Jin-woo Kwon; Jin A. Choi; Jung-sub Kim; Tae Yoon La (Journal of Ophthalmology)
Purpose. To assess the correlations of myopic β-zone parapapillary atrophy (β-PPA) with the optic nerve head (ONH) and retina. Methods. We selected 27 myopic patients who showed prominent β-PPA in one eye and no β-PPA in the other eye. We studied their macula, macular ganglion cell-inner plexiform layer (mGCIPL), peripapillary retinal nerve fiber layer (pRNFL) thickness, and ONH parameters using optical coherence tomography. Results. The average of five out of six sectors and minimum values of mGCIPL thicknesses in eyes with prominent β-PPA discs were significantly less than those of the control eyes. The results of clock-hour sector analyses showed significant differences for pRNFL thickness in one sector. In the ONH analyses, no significant difference was observed between myopic β-PPA and control eyes. The macular thickness of the β-PPA eyes was thinner than control eyes in all sectors. There was a significant difference between the two groups in three sectors (the inner superior macula, inner temporal macula, and inner inferior macula) but there was no significant difference in the other sectors, including the fovea. Conclusions. The myopic β-PPA eyes showed thinner mGCIPL, parafovea, and partial pRNFL layers compared with myopic eyes without β-PPA.